Process capability analysis of a 3D printing process. Issue 1 (2nd January 2020) - Siraj, Imran; Bharti, Pushpendra S.
Abstract: 3D printing processes (3DP) are getting wider applications in manufacturing, medical and socio-cultural sectors. Owing to involvement of various controllable and uncontrollable factors, many challenges are faced in terms of dimensions and shape of the object. In order to maintain quality under control, performance capability analysis (PCA) is used as a popular statistical tool in 3DP to ascertain how well the process meets a set of specification limits. The process under scanner is fused deposition modeling (FDM) type of 3DP. In PCA, process capability indices (PCI) are used to determine the quality that the process is delivering practically by calculating the deviation of the process mean from the target mean. This work employs PCA on FDM type 3DP by computing six PCIs in order to determine deviation of the process mean from target mean. This will help in determining the stability and the capability of the process. So, this work is an attempt to employ PCA to improve the quality of the 3DP process. Consideration of six PCIs is the novelty of the work.